Predicting cancer-related mycobiome aspects in gastrointestinal cancers: a systematic review - Szklenarik, György; Kiraly, Peter; Szegvari, Gabor; Dora, David; Lohinai, Zoltan (Frontiers in Medicine, 2024)
Background Colonization of the human gut and tumor tissue by non-pathogenic fungi has emerged as a potential risk factor associated with cancer epidemics. Therefore, we aimed to conduct a systematic review to assess the role of fungal colonization in gastrointestinal (GI) tumors in increasing diagnostic efficiency. Methods A PubMed citation search was conducted for publications up to and including March 2023, followed by full-text screening. Results were reported according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. According to the Patient, Intervention, Comparison, Outcome (PICO) framework, patients diagnosed with early-and advanced-stage GI cancers, GI adenoma patients, and healthy subjects were included with metagenomic (MG) or internal transcribed spacer (ITS) sequencing on tumor tissue, adjacent normal tissue, stool, and blood samples. Results Fourteen studies were eligible based on the inclusion criteria and methodological quality. Studies were conducted in stool (n = 8) or tissue (n = 7) as the most common specimens to be used for molecular analysis. In the collected data, ITS was used in n = 10 cases and metagenomic analyses in n = 3 cases. Observing the interindividual variability, we found that the Ascomycota/Basidiomycota (A/B) ratio from healthy to cancer state decreased in n = 2, increased in n = 1 cases, and did not change significantly in n = 2 studies. An increase in the relative abundance of Malassezia was identified in n = 4, of Candida in n = 5, of Saccharomyces in n = 2, and of Aspergillus in n = 2 cases. Intraindividual differences in the A/B ratio were identified in cancer and adjacent tissue (n = 4) and cancer vs. stool (n = 1) studies. Intraindividual variability of the A/B ratio showed an increase in n = 2 and no change in n = 3 studies for cancer tissue. Conclusion In conclusion, the advent of highly sensitive sequencing methods may aid in the identification and the differentiation of cancerous from healthy human fungal colonizations with potential future diagnostic applications. Further studies are needed to establish reliable biomarkers for GI cancer screening.